Polymorphism of prolactin, growth differentiation factor 9, and calpastatin genes and their effects on weight traits in Awassi lambs - Jawasreh, Khaleel Ibrahem; Ismail, Zuhair Bani (Journal of Advanced Veterinary and Animal Research, 2019)
Objectives: This study was conducted to determine the correlation among prolactin gene (PRG), growth differentiation factor 9 (GDF-9), and calpastatin (CAG) genes polymorphism with growth traits in Awassi lambs. Materials and Methods: Records of 779 Awassi lambs from 264 dams and 15 sires were used. The sex, type of birth (single versus twins), weight at birth, average daily gain (ADG), and the adjusted weight at 60 days of age were determined for each animal. Blood samples were collected from all lambs to determine PRG, GDF-9, and CAG polymorphism using polymerase chain reaction-Restriction fragment length polymorphism. Results: Three PRG genotypes (AA, AB, and BB) were determined with a frequency of 0.88, 0.05, and 0.07, respectively. The frequency of each allele was 0.84 and 0.16 for A and B alleles, respectively. For GDF-9, there were only two genotypes detected (AB and BB) with a frequency of 0.96 and 0.04, respectively. The frequency of each allele was 0.92 and 0.08 for A and B alleles, respectively. For CAG, two genotypes were also detected (AB and BB) with a frequency of 0.92 and 0.08, respectively. The frequency of each allele was 0.96 and 0.04 for A and B alleles, respectively. A significant (p ≤ 0.04) effect of PRG genotype on birth weight was detected but this effect was not significant on ADG and weight at weaning. There were no associations between any of the pre-weaning growth traits and GDF-9 and CAG variants. Conclusion: The results of this study show that PRG could be used to select dams with a high frequency of dystocia to reduce birth weight of newborn lambs and therefore conserve the dam’s reproductive functions and improve lamb survivability. J. Adv. Vet. Anim. Res., 6(1): 86-91, March 2019